The drop - Lehane, Dennis (William Morrow, 2014)
"Based on the screenplay he developed for Twentieth Century Fox from his short story "Animal Rescue," New York Times bestselling author Dennis Lehane's The Drop follows a former criminal whose efforts to build a new life with his girlfriend and pit bull rescue puppy fall apart when he becomes mixed up in a robbery gone wrong; scheduled for release in Fall 2014, Fox's film of the same title stars James Gandolfini (in his final on-screen performance), Tom Hardy, and Noomi Rapace"--